Pelaksanaan Pelayanan Prima Dalam Bidang Parkir Pada Koperasi Karyawan Kementerian Lingkungan Hidup Kehutanan Jakarta - Eka Putri Handayani; Resti Yulistria; Rosento; Dwi Fitriany (Jurnal Administrasi Bisnis, 2022)
Service is a matter that serves the needs of other people or customers, basically service is an attitude oriented to customers from product providers such as goods or services that have been offered to customers served. While excellent service can be interpreted as a pattern of service that sincerely serves the needs of others. Basically these services are intangible activities offered to consumers or customers they serve. So excellent service is closely related to service quality, customer satisfaction, and encouraging business process activities to return. This research was conducted using qualitative methods where data was obtained based on the results of observation, interviews, and documentation studies. The results of this study indicate that the implementation of Excellent Service in the field of parking at the Ministry of Forestry's Employees Cooperative feels satisfied because their needs have been fulfilled optimally, in the service procedures the officers provide good service, and are friendly to customers, and how to overcome obstacles that faced by the Ministry of Forestry's Employee Cooperative by providing good service to customers to feel satisfied because their needs have been fulfilled. Keyword: Excellent Service